Association Lp-PLA2 Gene Polymorphisms with Coronary Heart Disease. (2nd July 2022) - Ma, Sha; Ding, Liangcai; Cai, Mengdi; Chen, Lu; Yan, Bo; Yang, Jian
Abstract : Objectives . The study evaluated the association between lipoprotein-associated phospholipase A2 (Lp-PLA2) gene polymorphisms and coronary heart disease (CHD), in order to explore the molecular genetics of CHD. Methods . Groups of CHD patients (n = 283 ) and healthy controls (n = 261 ) were involved in this study. R92H, V279F, and A379V polymorphisms of LP-PLA2 gene were confirmed using polymerase chain reaction (PCR) and direct DNA sequencing. These polymorphisms and their interaction were also analyzed as potential risk factors of CHD. Results . In this study population, the genotypes of R92H (GG, GA, and AA), V279F (CC, AC, and AA) and A379V (GG, GA, and AA) were studied. There was a significantly difference in frequencies of R92H between CHD patients and controls (P < 0.05 ). In contrast, no significant difference in frequencies of V279F and A379V existed between CHD patients and controls. Furthermore, R92H and A379V were in strong linkage disequilibrium. Conclusions . These results suggested that R92H polymorphism might contribute to increased risk of CHD.